Fruit yield and root system distribution of 'Tommy Atkins' mango under different irrigation regimes - Marcelo R. dos Santos; Mauro A. Martinez; Sérgio L. R. Donato; Eugênio F. Coelho (Revista Brasileira de Engenharia Agrícola e Ambiental)
This study aimed to evaluate the fruit yield and the distribution of 'Tommy Atkins' mango root system under different irrigation regimes in the semiarid region of Bahia. The experimental design was completely randomized with five treatments and three replicates: 1 - Irrigation supplying 100% of ETc in phases I, II and III; 2 - Regulated deficit irrigation (RDI) supplying 50% of ETc in phase I (beginning of flowering to early fruit growth); 3 - RDI supplying 50% ETc in phase II (start of expansion until the beginning of physiological maturity); 4 - RDI supplying 50% ETc in phase III (physiological mature fruits); 5 - No irrigation during all three phases. The regulated deficit irrigation supplying 50% of the ETc during phase I and II provided larger root length density of 'Tommy Atkins' mango. Regardless of management strategy, the roots were developed in all evaluated soil volume and the highest density is concentrated from 0.50 to 1.50 m distance from the trunk and in 0.20 to 0.90 m depth in the soil, that suggests this region to be the best place for fertilizer application as well for soil water sensor placement. The application of RDI during fruit set does not influence either root distribution or production. Root system and crop production is significantly reduced under no irrigation conditions.